A Fuzzy-AHP Based Approach for Enhancing Network Selection in Heterogeneous Networks Using Battery Energy Criterion - Chattate, Imane; El Khaili, Mohamed; Bakkoury, Jamila (International Journal of Engineering and Technology, 2018)
Today, the rapid evolution of communication technologies requires a certain improvement of the quality of service (QoS) in order to meet the needs of the user. Vertical handover enables a mobile terminal to move from one network to another without loss of connection. Vertical handover management is one of major challenges to ensure seamless mobility in order to achieve efficient resource utilization while maintaining the quality of service (Qos). In this paper, we propose an approach for network selection based on the combination of AHP method with fuzzy logic including a new criterion which is the battery energy in order to reduce the number of executed handoffs, while extending the Mobile battery life. Performance results of the proposed system are also compared with those of the classical method, it is found that our proposed method outperforms the classical method with the highest relative standard deviation. Subsequently TOPSIS method is applied to rank the available networks.Â Â Â